1995
DOI: 10.1210/mend.9.3.7776977
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a prolactin-inducible gene, clone 15, in T cells.

Abstract: To examine how PRL regulates lymphocyte proliferation, a number of PRL-activated genes were identified from a PRL-dependent rat T lymphoma cell line, Nb2. One of the downstream genes in the PRL signaling cascade was identified as clone 15 (c15). PRL stimulation of quiescent Nb2 T cells results in the expression of a 1.7-kilobase c15 mRNA, which reaches maximum levels between 8 and 10 h after stimulation. Corresponding [3H]thymidine incorporation experiments show that the maximum level of c15 mRNA expression co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…NudC was isolated as an early growth-related gene in response to mitogenic stimulation by prolactin, suggesting that its expression is associated with cell proliferation (Axtell et al, 1995;Morris et al, 1997). Consistent with this initial observation, NudC expression is increased in various cell types undergoing mitosis (Gocke et al, 2000a, b) or stimulated to proliferate (Aumais et al, 2000;Gocke et al, 2000a, b), with high levels observed in leukemic cells and tumors (Aumais et al, 2000).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…NudC was isolated as an early growth-related gene in response to mitogenic stimulation by prolactin, suggesting that its expression is associated with cell proliferation (Axtell et al, 1995;Morris et al, 1997). Consistent with this initial observation, NudC expression is increased in various cell types undergoing mitosis (Gocke et al, 2000a, b) or stimulated to proliferate (Aumais et al, 2000;Gocke et al, 2000a, b), with high levels observed in leukemic cells and tumors (Aumais et al, 2000).…”
Section: Discussionmentioning
confidence: 70%
“…We previously identified NudC as an early response gene induced in mitogen-stimulated T cells (Axtell et al, 1995). Several studies show that elevated NudC levels correlate with the proliferative status of various cell types, tissues and tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If nuclear migration is essential for neuronal migration, it is reasonable to conclude that a defect in nuclear translocation is the cause of the neuronal migration defect observed in Miller-Dieker lissencephaly. An other gene, nudC, encodes a 22-kDa protein of unknown function, but it shows 68% identity to the C-terminal half of C15 protein, which was originally identified as a prolactin-inducible gene in activated T cells (24). Complementation experiments showed that the full-length mammalian (rat) C15 protein, which has a molecular mass of 45 kDa, is capable of rescuing the nuclear movement defect of nudC mutants (25) that the nudC protein regulates the nudF protein post-transcriptionally, suggesting that nudF and nudC proteins interact within cells.…”
Section: Discussionmentioning
confidence: 99%
“…In Vitro Transcription and Translation (TNT) of Stat5b-Stat5b and Stat5a were transcribed and translated in vitro using the T3 TNTcoupled reticulocyte lysate systems (Promega, Madison, WI) with 40 Ci of [ 35 S]methionine as described previously (25). 5 l of each reaction mixture was resolved by 7.5% SDS-polyacrylamide gel electrophoresis and analyzed by autoradiography to examine the size of Stat5b and Stat5a or used for immunoprecipitation with anti-Stat5b and antiStat5a Abs.…”
Section: Methodsmentioning
confidence: 99%